Motives for security and sexual activity among single individuals at the onset of the COVID-19 pandemic. Issue 1 (2nd January 2023) - Rodrigues, David L.; Balzarini, Rhonda N.; Zoppolat, Giulia; Slatcher, Richard B.
ABSTRACT: Amidst a global pandemic, survival needs become salient and the ability of individuals to regulate feelings and actions might be particularly relevant to protecting themselves from harm. Drawing from Regulatory Focus Theory individuals who are more focused on prevention are also more likely to enact health-protective behaviours, including sexual health behaviours, because they are more aware of threats. Extending this reasoning to the COVID-19 pandemic, we conducted a pre-registered longitudinal study with 174 individuals from 23 countries ( M age = 30.66, SD = 11.81; 77.6% women), to examine the role of regulatory focus in predicting the sexual activity of single individuals. We assessed demographic information, regulatory focus, and personality traits at baseline (T1), perceived threats two weeks later (T2), and sexual activity indicators two weeks later (T3). As hypothesised, results showed that single individuals who reported a greater focus on prevention at the onset of the pandemic perceived more pandemic-related threats and, in turn, reported less frequent sexual activity. These effects were consistent even when controlling for promotion (i.e. pleasure motives), personality, geographic location, local social distancing policies, gender, and sexual orientation. Findings are discussed considering their implications for the sexual functioning and sexual health of single individuals.